Catalytic Conversion of Cellulose to Levulinic Acid by Metal Chlorides - Beixiao Zhang; Junping Zhuang; Junhua Zhang; Lu Lin; Lincai Peng; Yan Gong (Molecules, 2010)
The catalytic performance of various metal chlorides in the conversion of cellulose to levulinic acid in liquid water at high temperatures was investigated. The effects of reaction parameters on the yield of levulinic acid were also explored. The results showed that alkali and alkaline earth metal chlorides were not effective in conversion of cellulose, while transition metal chlorides, especially CrCl3, FeCl3 and CuCl2 and a group IIIA metal chloride (AlCl3), exhibited high catalytic activity. The catalytic performance was correlated with the acidity of the reaction system due to the addition of the metal chlorides, but more dependent on the type of metal chloride. Among those metal chlorides, chromium chloride was found to be exceptionally effective for the conversion of cellulose to levulinic acid, affording an optimum yield of 67 mol % after a reaction time of 180 min, at 200 °C, with a catalyst dosage of 0.02 M and substrate concentration of 50 wt %. Chromium metal, most of which was present in its oxide form in the solid sample and only a small part in solution as Cr3+ ion, can be easily separated from the resulting product mixture and recycled. Finally, a plausible reaction scheme for the chromium chloride catalyzed conversion of cellulose in water was proposed.